Motivasi Tokoh Makunouchi Ippo menjadi Petinju dalam Anime Hajime no Ippo karya Jyoji Morikawa - Achmad Islachul Amri A D; Ketut Widya Purnawati; Renny Anggraeny (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
Motivation in achieving self-actualization often appears in literary works and popular media, including the Anime “Hajime no Ippo” by Jyoji Morikawa. The main character, Makunouchi Ippo, goes through a long journey to achieve self-actualization as a boxer, which is influenced by various factors that push him forward. This research aims to analyze how Ippo's motivation develops in his journey using a literary psychology approach and Maslow's (1943) hierarchy of needs theory. This research uses a descriptive qualitative method with a listening-recording technique, in which the data is analyzed based on dialogues and scenes in the Anime. The results of this study show that the most dominant motivation in Ippo's journey is the drive to achieve self-esteem. This motivation developed from personal experiences, such as the bullying she experienced, as well as support from the environment, such as gym mates, coaches, and family. In addition, Ippo's motivation was further strengthened after watching videos of boxing matches, which inspired him to become stronger and determined to prove himself. Ippo's motivation to become a professional boxer reflects the achievement of self-esteem and self-actualization needs in Maslow's hierarchy, which is key to his psychological journey in reaching his full potential